A cross‐cultural investigation of children's implicit attitudes toward White and Black racial outgroups. Issue 6 (14th May 2018) - Steele, Jennifer R.; George, Meghan; Williams, Amanda; Tay, Elaine
Abstract: Initial theory and research examining children's implicit racial attitudes suggest that an implicit preference favoring socially advantaged groups emerges early in childhood and remains stable across development (Dunham, Baron, & Banaji, 2008). In two studies, we examined the ubiquity of this theory by measuring non‐Black minority and non‐White majority children's implicit racial attitudes toward White and Black racial outgroups in two distinct cultural contexts. In Study 1, non‐Black minority children in an urban North American community with a large Black population showed an implicit pro‐White (versus Black) bias in early childhood. Contrary to previous findings, the magnitude of this bias was lower among older children. In Study 2, Malay (majority) and Chinese (minority) children and adults in the Southeast Asian country of Brunei, with limited contact with White or Black peers, showed an implicit pro‐White (versus Black) bias in early childhood. However, the magnitude of bias was greater for adults. Together, these findings support initial theorizing about the early development of implicit intergroup cognition, but suggest that context may affect these biases across development to a greater extent than was previously thought. A video abstract of this article can be viewed at:https://www.youtube.com/watch?v=vgQP8e4MSCk&feature=youtu.be Abstract : In two studies, we found that, consistent with initial theorizing, non‐Black minority children from Canada (Study 1), as well as non‐White majority and non‐Black minority children from Brunei (Study 2) showed an implicit pro‐White (versus Black) preference in early childhood. However, unlike previous theory and research, the magnitude of implicit pro‐White bias differed by age.